Changes in the supply and demand potentials of China's glacier water resources in the 21st century: Spatiotemporal mismatches and combined effects - Bo Su; Hong-Yu Zhao; Heng Ma; Can Zhang; Deliang Chen; Bin Chen; Yi Huang; Shi-Wei Liu; Tong Zhang; Cun-De Xiao (Advances in Climate Change Research, 2023)
China's glacier water resources (GWRs) are not only indispensable suppliers of fresh water for humans living in large domestic areas but also affect the water supply to downstream neighbouring countries. Therefore, it is crucial to systematically evaluate the spatiotemporal (mis-) matches between the supply and demand potentials of China's GWRs and the combined supply and demand effects in the 21st century to enable regional sustainable development. To facilitate such research, in this study, we first regionalized the importance of China's GWRs in terms of the supply potential and downstream human dependence to reveal the spatial (mis-) matches between supply and demand potentials. Then, changes in the service potential of glacier meltwater and in population dynamics, as well as their temporal (mis-) matches and associated opportunities and risks, were further assessed at the river basin scale. The results showed that GWR plays an important role in 4 of 16 macroscale glacier-fed basins (i.e., Tarim, Junggar, Ili, and Zangxi) and 11 of 37 subbasins within the China region due to higher supply potential and demand potential in those basins. The importance of China's GWRs increases dramatically when taking the demand potential of downstream countries into account, especially in the Ganges and Indus river basins. The peaks in meltwater runoff from the most glacierized basins of the eastern Tianshan Mountains, eastern Qilian Mountains, and southeastern Tibetan Plateau of China occur slightly earlier than the projected peak population (around 2030) under the mid-range Shared Socioeconomic Pathway (SSP245), leading to a compound risk in terms of decreasing meltwater supply and increasing human dependence at the end of the 2020s. However, the peak meltwater is expected to occur later than the peak population in the Tarim, Qiangtang Plateau, and Qaidam basins. The opportunities offered by the increase in meltwater can relieve the water resource pressure for those populations under water-stressed conditions. Greater attention should also be paid to water shortage risks in the transboundary river basins, especially in the Indus and Ganges basins, because the peak meltwater within China is generally expected to occur sooner than the projected peak population of downstream countries. This study provides an effective planning and decision-making basis for the full utilization of China's GWRs and adaptation when glacier runoff declines.